“Act, Object, Content: to Think Intentionality from Kazimierz Twardowski’s Work” - Niel, Luis (2015)
The  article  takes  as  a  point  of  departure  Brentano`s intentionalist  theory  and  its  problematic  distinction  between  intentional  and transcendent object, in order to present the way in which Twardowski reformulates these concepts by means of a differentiation between the content and the object of representations: on the one hand, the ‘content’ is the way of givenness of an object and fulfils an intermediary function between the act and its objective correlate; on the other hand, the ‘object’ is the necessary transcendent correlate of every representation, even of those, whose objects do not exist. In this context, it is the dimension of judgment that solves the problem of nonexistent objects. The final aim is to show how Twardowski presents an articulated theory that integrates an intentionalist theory of acts with a theory of objects and a philosophical semantics of sense (content).